2014
DOI: 10.1016/j.hrthm.2014.05.037
|View full text |Cite
|
Sign up to set email alerts
|

From beat rate variability in induced pluripotent stem cell–derived pacemaker cells to heart rate variability in human subjects

Abstract: Background We previously reported that induced Pluripotent Stem Cell-derived cardiomyocytes (iPSC-CM) manifest beat rate variability (BRV) resembling heart rate variability (HRV) in human sinoatrial node (SAN). We now hypothesized the BRV-HRV continuum originates in pacemaker cells. Objective To investigate whether cellular BRV is a source of HRV dynamics, we hypothesized three-levels of interaction among different cardiomyocyte entities: (1) single pacemaker cells, (2) networks of electrically coupled pacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 41 publications
7
41
1
Order By: Relevance
“…The importance of intracellular calcium pathways for the generation of BRV has recently been investigated in human ESC derived cardiomyocytes [6]. Consequently, the augmented BRV as a response to Verapamil in our in vitro model is consistent with clinical observations as well as in vitro studies in other species.…”
Section: Ivabradinesupporting
confidence: 87%
See 2 more Smart Citations
“…The importance of intracellular calcium pathways for the generation of BRV has recently been investigated in human ESC derived cardiomyocytes [6]. Consequently, the augmented BRV as a response to Verapamil in our in vitro model is consistent with clinical observations as well as in vitro studies in other species.…”
Section: Ivabradinesupporting
confidence: 87%
“…At the same time, an in vitro study, using human ESC-derived cardiomyocytes, concluded that 10 -6 M Ivabradine does not affect BRV [6]. In contrast to the experimental study, we detected a significant increase of all time domain measures when 10 -6 M Ivabradine was applied.…”
Section: Ivabradinecontrasting
confidence: 85%
See 1 more Smart Citation
“…Our data supports this conclusion and enables observation of their development over time. One particularly useful measure of cells' health is regularity of their beating cycle [34,37]. This measure is quantified by the Beating Regularity Index (BRI) histogram, which can be easily extracted from QPI data, and used for assessment of the cell viability and drug testing.…”
Section: Discussionmentioning
confidence: 99%
“…6(a). Irregular beating of single nodal hPSC-CMs has been linked to irregularity in the heart beat [37], and is an important indicator of drug toxicity [35]. The Beat Regularity Index (BRI), defined as the standard deviation of the beat period divided by the mean beat period, was calculated for 90 cells and its histogram is shown in Fig.…”
Section: Quantifying Cellular Activitymentioning
confidence: 99%